Professionalism in teaching and learning in higher education: learning from the basic teaching methodology programme - Othman, Azam; Mohin, Mohaida; Dahari, Zainurin (A S E A N Journal of Teaching and Learning in Higher Education, 2013)
This preliminary study focuses on academic staff’s perceptions and experiences on professional development opportunities in selected public universities in Malaysia. The research design involved the collection of semi-structured interview data from nine academic staff of three public universities. There are mixed reactions on academic staff’s receptivity on Basic Teaching Methodology Course (BTMC). The interview data revealed that academic participation in professional development brings encouraging changes in teacher knowledge, skills and ICT culture. Nevertheless, these changes are in substantial. The BTMC participants are still struggling to grasp the benefits of professional development. This situation is due to the heavy teaching workload among the lecturers. In addition, the academic staffs are expected to produce quality research and publication.